The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1038/s41598-018-29701-2
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Compound, “FA-1” Isolated from Prunus mume, Protects Human Bronchial Epithelial Cells and Keratinocytes from Cigarette Smoke Extract-Induced Damage

Abstract: Extract of the Japanese apricot (JAE) has biological properties as an antioxidant and anti-inflammatory agent. We hypothesized that JAE might exert therapeutic effects on cigarette smoke (CS)-induced DNA damage and cytotoxicity. In this study, we found that concentrated JAE protects against cigarette smoke extract (CSE)-induced cytotoxicity and DNA damage accompanied by increased levels of aldehyde dehydrogenase (ALDH)2, 3A1, and Werner’s syndrome protein (WRN) in immortalized human bronchial epithelial cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 38 publications
(48 reference statements)
0
9
0
Order By: Relevance
“…It is noteworthy that the antioxidant mixture of ascorbic acid (250 μΜ) with rutin (50 μΜ), which was used as reference, did not show any protection on keratinocytes (Figure 4), although the same concentrations as those described in literature were used (38)(39)(40). Moreover, known antioxidants such as resveratrol, and a furaldehyde isolated from the extract of the Japanese apricot which decrease lipid peroxidation derived aldehydes and N-acetyl cysteine which attenuated the damage provided by CS have been shown to partially protect skin cells from the oxidative effects of CS (36,41,42). However, the antioxidant-protective effect of Pinus halepensis bark extract seems to be even superior, since it is an agent able to absolutely inhibit oxidative stress or enhance viability even after the serious oxidative stress induced by CS-conditioned media (Figures 2-6).…”
Section: Discussionmentioning
confidence: 88%
“…It is noteworthy that the antioxidant mixture of ascorbic acid (250 μΜ) with rutin (50 μΜ), which was used as reference, did not show any protection on keratinocytes (Figure 4), although the same concentrations as those described in literature were used (38)(39)(40). Moreover, known antioxidants such as resveratrol, and a furaldehyde isolated from the extract of the Japanese apricot which decrease lipid peroxidation derived aldehydes and N-acetyl cysteine which attenuated the damage provided by CS have been shown to partially protect skin cells from the oxidative effects of CS (36,41,42). However, the antioxidant-protective effect of Pinus halepensis bark extract seems to be even superior, since it is an agent able to absolutely inhibit oxidative stress or enhance viability even after the serious oxidative stress induced by CS-conditioned media (Figures 2-6).…”
Section: Discussionmentioning
confidence: 88%
“…β(1,6)-branched oligosaccharides, as the products of MGAT5B, are well-known predictors of poor prognosis and decreased survival time in human cancers (32), which is consistent with our findings. In addition, ALDH3A1 has previously been correlated with cigarette smoke in airway epithelial cells (33). The correlation between these two metabolic genes and immune editing in the TME suggests that they should be the focus of further research.…”
Section: Discussionmentioning
confidence: 93%
“…Compounds derived from P. mume seeds also protected granulose cells from H 2 O 2 -induced apoptosis and promoted estradiol secretion (Kono et al, 2014). In a recent study, Jang et al (2018) found that a new compound isolated from P. mume increased the concentrations of aldehyde dehydrogenase (ALDH) and Werner's syndrome protein (WRN) in a dose-dependent manner and protected human bronchial epithelial cells and human epidermal keratinocytes from cigarette smoke-induced oxidative damage and DNA damage.…”
Section: Anti-inflammatory and Antioxidant Activitiesmentioning
confidence: 99%